La Biennale di Venezia : XXX Biennale internazionale d'arte 1960. - XXX Biennale internazionale d'arte, 1960 (Venezia : La biennale di Venezia, 1960)
Afro ; Giacomo Balla ; Willi Baumeister ; Julius Bissier ; Umberto Boccioni ; Constantin Brancusi, ; Georges Braque ; Alberto Burri ; Carlo Carrà ; Emil Cimiotti ; Pietro Consagra ; Robert Delaunay ; Piero Dorazio ; Agenore Fabbri ; Jean Fautrier ; Amedeo Fiorese ; Philip Guston ; Renato Guttuso ; Hans Hartung ; Hans Hofmann ; Franz Kline ; Mikhail Larionov ; Fernand Léger ; Leoncillo Leonardi ; August Macke ; Franz Marc ; Erich Mendelsohn ; Richard Mortensen ; Eduardo Paolozzi ; Victor Pasmore ; Antoine Pevsner ; Pablo Picasso ; Karl Schmidt-Rottluff ; Werner Schreib ; Kurt Schwitters ; Gino Severini ; Mario Sironi ; Rupert Stöckl ; Emilio Vedova ; Jacques Villon ; Ernst Weiers ; Giuseppe Zigaina
XXX Biennale internazionale d'arte 1960, 18.06 - 16.10.1960
Italiaans
kunstcatalogus